ANALYSIS OF FACTORS AFFECTING THE PURCHASE DECISION OF HEALTHYFOOD - Ariestiningsih, Eka Srirahayu; Syarifah Has, Dwi Faqihatus; Suprapti, Suprapti; Herawati, Arny; Latief, Thalita Syafa Syafiqoh (President University, 2023)
Healthy food is consumed to meet nutritional needs in accordance with health standards in order to increase intelligence and a healthy lifestyle. This study aims to determine the factors that most influence on healthy food buying decisions, from internal factors (age, lifestyle and knowledge) and external factors (product, promotion, price and place). In this research delimitation (restrictions) is carried out so that it is more controlled and relevant to what will be proven. The realization is that the age variable is not included in the factor analysis because it is a characteristic of the respondents, the place variable is also not analyzed because the marketing is done online. This correlational quantitative research uses primary and secondary data collected through interviews, documentation and questionnaires to 68 respondents, namely healthy food consumers. Data processing using the KMO-MSA method and interpretation of factor analysis, the results formed factor 1 (price, lifestyle, knowledge) and factor 2 (product and promotion). The Component Transformation Matrix shows the value of Component 1 and 2 whose correlation value is > 0.5, namely 0.735, it is concluded that the five variables are feasible for analysis. To find out the most influential factor, a multiple logistic regression test was carried out, the result is that the product has an Exp(B) value of 4.797, meaning that consumers have a tendency to buy because of the product 4.797 times. Meanwhile, promotions have an Exp(B) value of 8.991, meaning that consumers have a tendency to buy 8.991 because of promotions carried out by producers.